A Historical Review of Web Accessibility Using WAVE - Bhatia, Pooja Naresh; Malek, Sam (2024 IEEE/ACM Workshop on Gender Equality, Diversity, and Inclusion in Software Engineering (GEICSE), 2024)
In today's fast-evolving technology, the Internet has become an integral part of our everyday lives. However, for people with disabilities, accessing the online world and navigating through it can be a challenging task. Accessibility on the web ensures that the online world can be used by people with disabilities which is convenient and not complicated to use. The purpose of this study is to offer a thorough knowledge of how web accessibility has changed and evolved over the past ten years. In this historical review, leveraging website archives, patterns and insights in web accessibility over time has been researched. The study collected data on web accessibility violations between January 2013 and April 2023 from 40 homepages of websites across four popular website categories (social network, entertainment, e-commerce, and news media) in the United States using the WAVE subscription API. The data was then further analyzed and insights were found, such as the most common web accessibility issues, the best year for the web accessibility, and the effect of the website category on the levels of web accessibility issues. The study aims to provide insights on the current condition of web accessibility and identify areas that still require development. ACM Reference Format:Pooja Naresh Bhatia and Sam Malek. 2024. A Historical Review of Web Accessibility Using WAVE. In 2024 ACM/IEEE Workshop on Gender Equality, Diversity, and Inclusion in Software Engineering (GE@ICSE '24), April 20, 2024, Lisbon, Portugal. ACM, New York, NY, USA, 8 pages. https://doi.org/10.1145/3643785.3648489